Pengaruh Pendekatan Realistics Mathematics Education Berbantuan Squarec Smart terhadap Kemampuan Pemahaman dan Disposisi Matematis - Laila, Nur; Maulana, Maulana; Julia, Julia (Jurnal Pena Ilmiah, 2019)
The research aims to determine the increase in mathematical understanding and mahematicalÂ  disposition of students who study with the Realistics Mathematics Education (RME) approach with Squarec Smart, compare it to conventional learning, and knowing the relationship between mathematical understanding and disposition. This research used quasi-experimental method with nonequivalent control group design. The population is all class IV in Sumedang Selatan Subdistrict with samples of class IVA (experiment) and IVB (control) in SDN Sukaraja I. The results of this research show that learning with the RME approach assisted by Squarec Smart and convensional learning both increase mathematical understanding and disposition. However, the RME with Squarec Smart significantly improved mathematical understanding and mathematical disposition compared to the conventional approach. In addition, the result show that there is no correlation between mathematical understanding and mathematical disposition.